ANALISIS YURIDIS HAK INGKAR NOTARIS DALAM TINDAK PIDANA KORUPSI - KISWANTO, HERY ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The purpose of this study was to assess the dissenter rights against Law No. 2 of 2014 on the amendment of Act No. 30 of 2004 and examines the application of Notary’s dissenter rights in the law enforcement of corruption by decision No. 20 / PID.SUS / TPK /2013/PN.JKT.PST. This research is a normative law that refers to the norms and principles of law contained in the legislation. This study is descriptive because it wants to reveal the truth right to break a law concerning arrangements notary in the notary's practice in Indonesia and how should the exercise dissenter on the notary law enforcement of corruption. Primary data sources obtained from interviews and secondary data sources were obtained from official documents, the books, the results of other studies related to the object of research. Data were analyzed with qualitative methods and then presented descriptively by describing and outlining in accordance with the problems associated with the research. The notary’s dissenter rights contained the oath of notary who ordered to keep the contents of the deed provided for in Article 4 and Article 16 letter f Law No. 2 of 2014 on changes UUJN No. 30 of 2004, it is also stipulated in Article 322 paragraph (1) of the Criminal Code. These two Articles shall not apply if the other Act ordered to give confidential information and provide information / statement to those who request it. Notary as witness who participate can not use dissenter rights in accordance with the provisions of Article 21 of the Law on Corruption Eradication, broken Rights can not be implemented due to related criminal acts of corruption specifically by using the principle of \"lex specialis legi generali derogat\". Implementation of a notary’s dissenter rights in the case of Decision Number: 20 / PID.SUS / TPK / 2013 / PN.JKT.In PST, there are 15 (fifteen) Notary as a witness, 14 (fourteen) did not apply the Notary’s dissenter rights during court proceedings , notaries does not know that all of the objects owned by the DS on behalf of other parties with the aim of hiding the assets acquired from the proceeds of corruption while one (1) person who is also a notary witness does not apply dissenter rights during investigation and trial process , this is done by the notary because the notary knew about using the other side on an object but the notary doesn’t know the origin of the source of funds and purpose of the DS.